MENGUNGKAP KECURANGAN PENCATATAN PERSEDIAAN BARANG STUDI KASUS PADA PT. AGUNG AQUATIC MARINE - Ibraraharie, Maharditya Nanda; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to comprehend and to analyze how the implementation of the internal control system in the goods inventory procedures and to analyze whether the internal control of goods inventory can decrease fraud on the inventory recording. This research applies qualitative data analysis in which the data analysis has been carried out by conducting observation, interviews and documentation The result of discussion and analysis is the existence of excess of functions which has been performed by the receiving department and warehouse department. Then there is a fraud that has been committed by the warehouse department in the product packaging process which is done by using Styrofoam, carton and plastic, and the last problem is there is no accurate information about the availability of goods in the warehouse. The conclusion of these problems which are faced by PT. Agung Aquatic Marine is the process of inventory recording that is the organizational structure of the company is incomplete so that the excess of functions occur, then lack of supervisory about the warehouse department or the activity of the companyKeywords: Fraud, Inventory, Internal Control.